Interactive Science Media Innovation Based on Deep Learning Approach Integrated with Tri-N to Enhance Elementary School Students' Critical Thinking Skills - Pardimin Pardimin; Ana Fitrotun Nisa; Wahyu Dwi Herawati (Prodi Pendidikan Fisika Universitas Sarjanawiyata Tamansiswa, 2026)
This study aimed to develop an interactive science media innovation based on deep learning approach integrated with Tri-N and to evaluate its validity, practicality, and effectiveness in improving elementary school students' critical thinking skills. This study employed a Research and Development (R&D) design using ADDIE model, which consists of five stages: Analysis, Design, Development, Implementation, and Evaluation. The participants were fifth-grade elementary school students, involving 20 students in the pilot trial and 62 students in the field trial. Data were collected through observations, interviews, questionnaires, tests, and documentation, and were analyzed using descriptive qualitative and quantitative techniques. The results indicated that the developed interactive science learning medium was designed based on the principles of deep learning, emphasizing mindful, meaningful, and joyful learning, and integrated with Tri-N learning activities of niteni (careful observation), nirokke (imitation or replication), and nambahi (modification or improvement). Validation results showed that the developed media was considered valid, receiving a score of 98.57% from media experts and 87.62% from subject matter experts. The practicality test demonstrated that the media was highly practical, achieving a score of 93.63%. Furthermore, the effectiveness test revealed that the developed media significantly improved students' critical thinking skills, as indicated by the results of paired-samples t-test (0.001 < 0.05), the independent-samples t-test (0.008 < 0.05), and an N-Gain score of 0.75, which falls into the high category. Based on these findings, it can be concluded that interactive science media based on deep learning approach integrated with Tri-N approach is valid, practical, and effective in enhancing elementary school students' critical thinking skills.